Mechanical behavior of alpha titanium alloys at high strain rates, elevated temperature, and under stress triaxiality - Skripnyak, Vladimir V. (Metals)
The paper presents the experimental results of the mechanical behavior of Ti-5Al-2.5Sn alloy at high strain rates and elevated temperature. Flat smooth and notched specimens with notch radii of 10 mm, 5 mm, and 2.5 mm were used. The experimental studies were carried out using the high-velocity servo hydraulic test machine Instron VHS 40/50-20. The samples were heated with flat ceramic infrared emitters on average between 60 s and 160 s. The temperature control in the working part of specimens was carried out in real time using a chromel-alumel thermocouple. The digital image correlation (DIC) method was employed to investigate the evolution of local fields in the gauge section of the specimen. Data on the influence of stress triaxiality on the ductility of Ti-5Al-2.5Sn alloy were obtained under tension with strain rates ranging from 0.1 to 10(3) s(-1) at a temperature of 673 K. It was found that, at 673 K, the ductility of Ti-5Al-2.5Sn alloy increases with the increasing strain rate for both smooth and notched specimens.